Fmr1 KO Mice as a Possible Model of Autistic Features - Maude Bernardet; Wim E. Crusio (The Scientific World Journal)
Autism is a pervasive developmental disorder appearing before the age of 3, where communication and social interactions are impaired. It also entails stereotypic behavior or restricted interests. Although this disorder was first described in 1943, little is still known about its etiology and that of related developmental disorders. Work with human patients has provided many data on neuropathological and cognitive symptoms, but our understanding of the functional defects at the cellular level and how they come about remains sketchy. To improve this situation, autism research is in need of valid animal models. However, despite a strong hereditary component, attempts to identify genes have generally failed, suggesting that many different genes are involved. As a high proportion of patients suffering from the Fragile X Syndrome show many autistic symptoms, a mouse model of this disorder could potentially also serve as a model for autism. The Fmr1 KO mouse is a valid model of the Fragile X Syndrome and many data on behavioral and sensory-motor characteristics of this model have been gathered. We present here an assessment of autistic features in this candidate model. We conclude that Fmr1 KO mice display several autistic-like features, but more work is needed to validate this model.